MRI Highly Accelerated Wave‐CAIPI T1‐SPACE versus Standard T1‐SPACE to detect brain gadolinium‐enhancing lesions at 3T. Issue 5 (3rd June 2021) - Goncalves Filho, Augusto Lio M.; Longo, M. Gabriela Figueiro; Conklin, John; Cauley, Stephen F.; Polak, Daniel; Liu, Wei; Splitthoff, Daniel N.; Lo, Wei‐Ching; Kirsch, John E.; Setsompop, Kawin; Schaefer, Pamela W.; Huang, Susie Y.; et al.
Abstract: Background and Purpose: High‐resolution three‐dimensional (3D) post‐contrast imaging of the brain is essential for comprehensive evaluation of inflammatory, neoplastic, and neurovascular diseases of the brain. 3D T1‐weighted spin‐echo‐based sequences offer increased sensitivity for the detection of enhancing lesions but are relatively prolonged examinations. We evaluated whether a highly accelerated Wave‐controlled aliasing in parallel imaging (Wave‐CAIPI) post‐contrast 3D T1‐sampling perfection with application‐optimized contrasts using different flip angle evolutions (T1‐SPACE) sequence (Wave‐T1‐SPACE) was noninferior to the standard high‐resolution 3D T1‐SPACE sequence for visualizing enhancing lesions with comparable diagnostic quality. Methods: One hundred and three consecutive patients were prospectively evaluated with a standard post‐contrast 3D T1‐SPACE sequence (acquisition time [TA] = 4 min 19 s) and an optimized Wave‐CAIPI 3D T1‐SPACE sequence (TA = 1 min 40 s) that was nearly three times faster than the standard sequence. Two blinded neuroradiologists performed a head‐to‐head comparison to evaluate the visualization of enhancing pathology, perception of artifacts, and overall diagnostic quality. A 15% margin was used to test whether post‐contrast Wave‐T1‐SPACE was noninferior to standard T1‐SPACE. Results: Wave‐T1‐SPACE was noninferior to standard T1‐SPACE for delineating parenchymal and meningeal enhancing pathology ( p  < 0.01). Wave‐T1‐SPACE showed marginally higher background noise compared to the standard sequence and was noninferior in the overall diagnostic quality ( p = 0.03). Conclusions: Our findings show that Wave‐T1‐SPACE was noninferior to standard T1‐SPACE for visualization of enhancing pathology and overall diagnostic quality with a three‐fold reduction in acquisition time compared to the standard sequence. Wave‐T1‐SPACE may be used to accelerate 3D post‐contrast T1‐weighted spin‐echo imaging without loss of clinically important information.